1998
DOI: 10.1542/peds.102.6.1415
|View full text |Cite
|
Sign up to set email alerts
|

Injuries to Children With Attention Deficit Hyperactivity Disorder

Abstract: Injured children with ADHD are more likely to sustain severe injuries than are children without ADHD. More research is needed to identify prevention efforts specifically targeted at this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
197
2
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(223 citation statements)
references
References 21 publications
15
197
2
5
Order By: Relevance
“…Firstly, more children with ADHD were likely to have sustained injuries needing hospitalization, 85.2% vs 50%, indicating the possibility that the injuries were more severe. This finding is supported by other studies in similar accident and emergency settings 7 . In contrast, a study of preschoolers with ADHD found that they were more at risk of minor injuries but not major injuries when compared to a control group of non-ADHD children 16 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Firstly, more children with ADHD were likely to have sustained injuries needing hospitalization, 85.2% vs 50%, indicating the possibility that the injuries were more severe. This finding is supported by other studies in similar accident and emergency settings 7 . In contrast, a study of preschoolers with ADHD found that they were more at risk of minor injuries but not major injuries when compared to a control group of non-ADHD children 16 .…”
Section: Discussionsupporting
confidence: 90%
“…Our study also shows a proportionately higher number of fractures and head injury in children diagnosed with ADHD when compared to children without ADHD, though not a statistically significant difference. Similar findings are reported on association between ADHD and selected injury type such as head injury, burns and other trauma 7,9 . It was interesting to note that proportionately more children without ADHD had learning difficulties though this is a known comorbidity with ADHD.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is especially pertinent given data that children with ADHD are reported to sustain higher levels of injury, especially CHI, when compared with age-matched controls. 5 This study may better inform the clinical management in children who have ADHD and experience a CHI, perhaps directing more intensive resources and closer monitoring to encourage maximal recovery. Third, it may spur the education of families of children with ADHD about expectations during the recovery period after TBI.…”
mentioning
confidence: 95%